The keepers of the temple - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The costs of maintenance and cleaning in a market can be expensive for traders when the work is carried out by council services. In Bobo, the costs of h 4,500 are shared out on the basis of the space occupied by each trader. In the Yeoville market...